Graphene FET Array Biosensor Based on ssDNA Aptamer for Ultrasensitive Hg2+ Detection in Environmental Pollutants - Tu, Jiawei; Gan, Ying; Liang, Tao; Hu, Qiongwen; Wang, Qian; Ren, Tianling; Sun, Qiyong; Wan, Hao; Wang, Ping (Frontiers in Chemistry, 2018)
Invisible mercury ion is an extremely poisonous environmental pollutant, therefore, a fast and highly sensitive detection method is of significant importance. In this study, a liquid-gated graphene field-effect transistor (GFET) array biosensor (6×6 GFETs on the chip) was fabricated and applied for Hg2+ quantitate detection based on single-stranded DNA (ssDNA) aptamer. The biosensor showed outstanding selectivity to Hg2+ in mixed solutions containing various metal ions. Moreover, the sensing capability of the biosensor was demonstrated by real-time responses and showed a fairly low detection limit of 40 pM, a wide detection ranged from 100pM to 100nM and rapid response time below one second. These results suggest that the GFET array biosensor based on ssDNA aptamer offers a simple fabrication procedure and quite fast method for mercury ion contaminant detection and are promising for various analytical applications.